Relative abundance of snapper (Chrysophrys auratus) across habitats within an estuarine system. Issue 3 (2nd July 2016) - Parsons, DM; Buckthought, D; Middleton, C; MacKay, G
ABSTRACT: Many fish species rely on estuarine nursery habitats as they transition to adult life stages. Quantifying nursery value, however, requires identification of the life stages (often small and short-lived) that utilise nursery habitats, and survey methods that provide comparable estimates across habitats. We focused our surveys on post-settlement snapper ( Chrysophrys auratus ) using video camera deployments across habitats within a northeastern New Zealand harbour. Post-settlement snapper abundance was higher among structured habitat types relative to bare sediments, with the type of structured habitat not influential. The exception appeared to be for reef habitat (although sampling was limited). Reef sites were structurally complex, but largely inhabited by older life stages (snapper and other fish species). Overall, nursery value for snapper appears to be connected to structure, rather than structure type. This result emphasises the importance of a broadened scope to coastal fishery management, one that incorporates not just fish extraction, but also habitat maintenance or restoration.